PENERAPAN MAKE UP SPESIAL EFEK DALAM FILM “GERING” - Kadek Meishya Paraswari Putri; I Wayan Mudra; I Gusti Ngurah Wirawan (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The Covid-19 pandemic is a phenomenon that is happening all over the world, especially in Bali, the Covid-19 disease that causes the virus to suddenly enter the human body. Currently, the government is actively trying to vaccinate evenly to all people. The phenomenon of the Covid-19 pandemic became the basic idea in the film entitled